(untitled) (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2025)
This article explains magical characters and their narrative functions in English and Uzbek folk tales. The research focuses on identifying the main types of magical characters, such as heroes, helpers, villains, and supernatural beings, and analyzing their roles within the plot structure. The study examines selected English folk tales and Uzbek folk tales to reveal similarities and differences in the representation and function of magical characters.